Effectiveness of Lead and Cadmium Reduction with Adsorption Method using a Combination of Chitosan and Coffee Grounds (Case Study of Industrial Wastewater PT.X Indonesia) - Nisa Nurhidayanti; Nur Ilman Ilyas; Dhonny Suwazan (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
PT. X Indonesia (PXI) is a company engaged in laboratory services in Bekasi Regency. Based on a preliminary study, the concentration of cadmium and lead in wastewater shows that it exceeds the quality standard of PerMenLHK No. P12 of 2020. The presence of cadmium and lead in PXI's wastewater must be resolved immediately to avoid dangerous human activities and polluting the environment. The research was initiated by taking wastewater samples and synthesizing the adsorbent from the combination of chitosan and activated carbon from coffee grounds. The method used in this study is an experimental approach with quantitative descriptive methods based on laboratory data using FT-IR, SEM EDX and AAS instruments. The results showed that chitosan biosorbent and 1.4-gram coffee grounds activated carbon resulted in the highest cadmium metal reduction efficiency of 94.35% and led to a metal reduction efficiency of 90.86%. The results concluded that the adsorbent of chitosan-activated carbon coffee grounds is very effective in reducing cadmium and lead metals in the wastewater of PXI. This research needs to follow up by increasing the mass of activated carbon of coffee grounds to meet quality standards.